2010
DOI: 10.1186/1743-422x-7-75
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A viral loads in respiratory samples collected from patients infected with pandemic H1N1, seasonal H1N1 and H3N2 viruses

Abstract: BackgroundNasopharyngeal aspirate (NPA), nasal swab (NS), and throat swab (TS) are common specimens used for diagnosis of respiratory virus infections based on the detection of viral genomes, viral antigens and viral isolation. However, there is no documented data regarding the type of specimen that yields the best result of viral detection. In this study, quantitative real time RT-PCR specific for M gene was used to determine influenza A viral loads present in NS, NPA and TS samples collected from patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 11 publications
2
47
0
1
Order By: Relevance
“…The intra-laboratory variability (CV) was lower than 5% in all dilutions and the inter-laboratory variability ranged from 0.92% to 2.70%. The Ct values and the standard curve equation were in agreement with data presented by Ngaosuwankul et al 2 A total of 120 respiratory samples (30 from each center) were quantified by comparison of Ct values with usual locally generated standard curves and using the VQT. The median copy number according to the locally generated standard curve was 2.5 × 10 5 RNA copies/ml sample (range 1.9 × 10 2 to 5.4 × 10 8 RNA copies/ml sample) while according to VQT was 3.1 × 10 5 RNA copies/ml sample (range 1.7 × 10 2 to 6.3 × 10 8 RNA copies/ml sample).…”
Section: Resultsmentioning
confidence: 99%
“…The intra-laboratory variability (CV) was lower than 5% in all dilutions and the inter-laboratory variability ranged from 0.92% to 2.70%. The Ct values and the standard curve equation were in agreement with data presented by Ngaosuwankul et al 2 A total of 120 respiratory samples (30 from each center) were quantified by comparison of Ct values with usual locally generated standard curves and using the VQT. The median copy number according to the locally generated standard curve was 2.5 × 10 5 RNA copies/ml sample (range 1.9 × 10 2 to 5.4 × 10 8 RNA copies/ml sample) while according to VQT was 3.1 × 10 5 RNA copies/ml sample (range 1.7 × 10 2 to 6.3 × 10 8 RNA copies/ml sample).…”
Section: Resultsmentioning
confidence: 99%
“…• Nasal swab Although a nasopharyngeal aspirate (NPA) is considered to be the best specimen for detecting influenza A viruses, [53][54][55] this procedure causes more discomfort and is more difficult to perform, particularly in children. Indeed, studies attempting to collect daily NPA samples from subjects have reported problems with subjects' tolerance and compliance with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive and specific TaqMan assay targeting a single nucleotide polymorphism within the NP gene has been described that can differentiate pandemic H1N1 from other swine virus [45]. Recently, a quantitative RT-PCR targeting the M gene was used to compare the pandemic H1N1 viral loads in NP, NPA and throat swab samples from 12 patients [46]. NPA was found to contain the highest amount of virus followed by nasal swab and throat swab.…”
Section: Swine-origin Influenza H1n1 2009mentioning
confidence: 98%